Distillation of mallee biomass for eucalyptus oil extraction and thermochemical behaviour of the spent biomass - Yani, Syamsuddin (Curtin University, 2015)
This thesis investigates eucalyptus oil extraction, nutrients release, carbon loss and structural changes of mallee leaf after steam distillation. Pyrolysis of the spent leaf was then conducted to study the biochar characteristics. The mallee leaf was also torrefied then combusted under pulverised fuel (PF) condition for examining the effect of torrefaction on particulate matter emission. The obtained knowledge and data significantly contribute to developing a mallee-based bioenergy system in the rural and regional Australia.